Physician education and report cards: do they make the grade? Results from a randomized controlled trial - Kim, Caroline S; Kristopaitis, Raymond J; Stone, Erin; Pelter, Mitchell; Sandhu, Meenu; Weingarten, Scott R (The American journal of medicine, 1999)
PURPOSE: We sought to determine whether tailored educational interventions can improve the quality of care, as measured by the provision of preventive care services recommended by the US Preventive Services Task Force, as well as lead to better patient satisfaction. SUBJECT AND METHODS: We performed a randomized controlled study among 41 primary care physicians who cared for 1,810 randomly selected patients aged 65 to 75 years old at Kaiser Permanente Woodland Hills, a group-model health maintenance organization in southern California. All physicians received ongoing education. Physicians randomly assigned to the comprehensive intervention group also received peer-comparison feedback and academic detailing. Baseline and postintervention (2 to 2.5 years later) surveys examining the provision of preventive care and patient satisfaction were performed and medical records were reviewed. RESULTS: Based on the results of patient surveys, there were significant improvements over time in the provision of preventive care in both the education and the comprehensive intervention groups for influenza immunization (79% versus 89%, P <0.01, and 80% versus 91%, P <0.01), pneumococcal immunization (42% versus 73%, P <0.01 and 34% versus 73%, P < 0.01), and tetanus immunization (64% versus 72%, P <0.01, and 59% versus 79%, P <0.01). Mammography (90% versus 80%, P <0.01) and clinical breast examination (85% versus 79%, P <0.05) scores worsened in the education only group but not in the comprehensive intervention group. However, there were few differences in rates of preventive services between the groups at the end of the study, and the improvements in preventive care were not confirmed by medical record review. Patient satisfaction scores improved significantly in the comprehensive intervention group (by 0.06 points on a 1 to 5 scale, P = 0.02) but not in the education only group (by 0.02 points, P = 0.42); however, the improvement was not significantly greater in the comprehensive intervention group ( P = 0.20). CONCLUSION: A physician-targeted approach of education, peer-comparison feedback, and academic detailing has modest effects on patient satisfaction and possibly on the offering of selected preventive care services. The lack of agreement between patient reports and medical records review raises concerns about current methods of ascertaining compliance with guidelines for preventive care.